Local Natural Product Development in the Era of Covid 19 Pandemic - Noval, N; Nugraha, Dyan Fitri; Nastiti, Kunti; Syahrina, Dahlia; Novia, N (UKInstitute, 2021)
Covid-19 is a pandemic disease that infects the respiratory system by cough and sneeze. Covid 19 infection rate in Indonesia is high. On March 2nd 2020, there was reported 2 confirmed cases of Covid-19 infection. Natural ingredients contain a secondary metabolite compound has the potential as an antimicrobial that can be used to kill microorganism as a source of the disease. Natural ingredients that are commonly used as antimicrobials such as bundung, betel leaf and lime peel. Pharmaceutical formulations from natural ingredients need to be made to obtain preparations that are beneficial to the community because they are safer and have minimal side effects. Based on this description, it is necessary to conduct training on the manufacture of pharmaceutical products from natural ingredients or local resources that are easy to make so it can be useful and beneficial for the community during the Covid-19 pandemic. The activities were carried out virtually, followed by the teacher council and students from High School 1 Kahayan Hilir. The activities carried out by providing information related to the efficacy of natural ingredients from local resources, training or workshops on the manufacture of pharmaceutical products and education regarding storing and how to use drugs correctly. This activity is expected to be useful and make a big contribution to the community during the Covid-19 pandemic.